Unitary model for atomic ionization by an intense laser pulse - Bustamante Pilone, Manuel Guillermo (2009)
A unitary model describing the electronic transitions in an atom interacting with a laser pulse is proposed. The model includes the initial state coupling with the continuum spectrum. Continuum-continuum transitions are neglected although transitions from the initial state to other discrete states within the first Born approximation are considered. The model leads to a single integro-differential equation for the initial state amplitude which is numerically solved. The results are compared with TDSE simulations for Hydrogen atoms.